Struktur dan Fungsi Kepeminpinan YPDPA Sumut (International Forum of Researchers and Lecturers, 2023)
YPDPA was formed due to a desire to spread the good news in general in North Sumatra to students. YPDPA believes in salvation that salvation is not the result of our work or our efforts but because of God's gift. This study aims to determine the structure and function of YPDPA's leadership in Tarutung, to be precise at Perumnas. The method used by the author is descriptive qualitative method. The results of the research revealed that the YPDPA leadership structure existed in each district/city and assigned one person as coordinator in the sector section. For the leadership function in the sector carry out tasks according to directions from the YPDPA head office.